Search for viruses in rheumatoid macrophage-rich synovial cell populations. Issue 2 (April 1980) - Hart, H; Norval, M
Abstract : The adherent cells remaining after short-term culture of synovial fluid and synovial membrane cells from rheumatoid and non-rheumatoid patients were examined for the presence of a productive virus infection and for various viral antigens. Labelling was carried out with 3H-thymidine and 3H-uridine followed by sucrose density gradient centrifugation of the culture supernatant. Only in 1 case was there incorporation of 3H-uridine into material of density 1 . 21 g/cm3. Viral antigens were tested for by indirect immunofluorescence with antisera to rubella virus, the retroviruses RD-114 and simian sarcoma associated virus, early adenovirus type 2 antigens, late adenovirus type 2 antigens, SV-40 T antigen, and in 1 case measles virus. No cell showed immunofluorescence with any antiserum except the early adenovirus type 2 antiserum, which stained the cytoplasm of about half the synovial cell cultures, some from rheumatoid and some from non-rheumatoid patients.